Nigeria : the first 25 years - Eleazu, Uma O (ed.) (Lagos : Infodata Ltd. ; Ibadan : in association with Heinemann Educational Books (Nigeria), 1988)
This volume provides a panorama of events of the first twenty five years. It also provides a baseline on which to judge the next twenty five years, and through that through that suggests a more realistic way of looking at progress
Includes bibliographical references.
ijb, 17/01/2019
Loans
Keywords: History - Nigeria; Nigeria; Nigeria